Manchu-Mongol Relations on the Eve of the Qing Conquest : A Documentary History - Cosmo, Nicola Di; Bao, Dalizhabu (BRILL, 2003)
In the seventeenth century the Manchu conquered the whole of China, replacing the Ming dynasty. The original Manchu and Mongol documents selected for the this publication, translated and amply annotated, provide fascinating new information about the relations between Manchus and Mongols before the Manchu conquest of China. They include diplomatic correspondence, military liaisons, legal cases, and records of tribute missions and present a detailed picture of the relative position of the various Mongol tribes vis-à-vis the future emperors of China.
Keywords: International relations.; Mongolian.; Mongols -- History -- Sources.; China -- History -- Li Zicheng Rebellion, 1628-1645 -- Sources.; Relations internationales.; Mongols -- Histoire -- Sources.; Chine -- Histoire -- 1628-1645 (Rébellion de Li Zicheng) -- Sources.; international relations.; International relations; Mongols; China; 1628-1645; History; Sources